Effect of CGRP inhibitors on interictal cerebral hemodynamics in individuals with migraine - Carter, Sarah C.; Cucchiara, Brett; Reehal, Navpreet; Hamilton, Katherine; Kaiser, Eric A.; Favilla, Christopher G. (Frontiers in Neurology, 2024)
Introduction: Calcitonin gene-related peptide (CGRP) plays an important role in cerebral vasodilation, so here we aim to quantify the impact of CGRP monoclonal antibody (mAb) therapy on cerebral hemodynamics.In 23 patients with chronic and episodic migraine, cerebral hemodynamic monitoring was performed (1) prior to and (2) 3-months into CGRP-mAb therapy. Transcranial Doppler monitored cerebral blood flow velocity (CBFv) in the middle cerebral artery (MCA) and posterior cerebral artery (PCA), from which cerebrovascular reactivity (CVR) and cerebral autoregulation (CA; Mxindex) were calculated.Results: CA was similar off and on treatment, in the MCA (p=0.42) and PCA (p=0.72). CVR was also unaffected by treatment, in the MCA (p=0.38) and PCA (p=0.92). CBFv and blood pressure were also unaffected. The subgroup of clinical responders (>50% reduction in migraine frequency) exhibited a small reduction in MCA-CBFv (6.0 cm/sec; IQR: 1.1-12.4; p=0.007) and PCA-CBFv (8.9 cm/sec; IQR: 6.9-10.3; p=0.04).Discussion: Dynamic measures of cerebrovascular physiology were preserved after 3 months of CGRP-mAb therapy, but a small reduction in CBFv was observed in patients who responded to treatment. Subgroup findings should be interpreted cautiously, but further investigation may clarify if CBFv is dependent on the degree of CGRP inhibition or may serve as a biomarker of drug sensitivity.